2021
DOI: 10.1136/bmjopen-2021-053395
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the factors affecting the adoption and compliance of the NHS COVID-19 mobile application: a national cross-sectional survey in England

Abstract: ObjectivesTo conduct an independent study investigating how adults perceive the usability and functionality of the ‘National Health Service (NHS) COVID-19’ application (app). This study aims to highlight strengths and provide recommendations to improve adoption of future contact tracing developments.DesignA 60-item, anonymous online questionnaire, disseminated through social media outlets and email lists by a team from Imperial College London.SettingEngland.ParticipantsConvenience sample of 1036 responses, fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
(28 reference statements)
2
18
0
Order By: Relevance
“…51 Several studies reported on the public's concerns about data privacy and whether data would be shared with other organizations. [32][33][34] Participants in our study appeared to be reassured about data privacy, as the data are held under the governance framework of NHS Scotland, which is generally regarded as a trustworthy organization.…”
Section: Comparison With Previous Literaturementioning
confidence: 87%
“…51 Several studies reported on the public's concerns about data privacy and whether data would be shared with other organizations. [32][33][34] Participants in our study appeared to be reassured about data privacy, as the data are held under the governance framework of NHS Scotland, which is generally regarded as a trustworthy organization.…”
Section: Comparison With Previous Literaturementioning
confidence: 87%
“…Another study conducted in the United States found that the MyCOVIDKey app was a useful tool for COVID-19 contact tracing, but it needed simple modifications to improve usability [ 32 ]. Similarly, in a study carried out in England, participants viewed the NHS COVID-19 app positively [ 33 ]. However, the respondents considered that the interface was challenging, difficult, and complex.…”
Section: Discussionmentioning
confidence: 99%
“…However, the respondents considered that the interface was challenging, difficult, and complex. They thought that these factors would limit its use by the UK population (79) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 This figure is greater than the COVID-19 contact-tracing apps in Japan (21.3%) but lower than the NHS COVID-19 mobile apps in the United Kingdom (84.1%). 26,27 According to study in Germany, offering incentives improved the adoption of a COVID-19 contact-tracing apps. 28 This study showed that most respondents used the PL 25 One of influential factors on the frequency of the apps by respondents while visiting public facilities is strict monitoring by officers on duty.…”
Section: Discussionmentioning
confidence: 99%
“…However, insufficient knowledge of the aapps's functionality and privacy concerns may influence their decision not to use it. 27 Respondents also considered that the information generated by the apps was unreliable. Accord ing to one study, the zone information status displays different information if used on two separate devices in the same region.…”
Section: Discussionmentioning
confidence: 99%